The Impact of Nursing Management Information Systems on Workload and Effectiveness of Inpatient Nursing Services - Novi Triwanto; Astrid Novita; Adi Wijaya; Ade Suhendri (Borneo Scientific Publishing, 2026)
The implementation of the Nursing Management Information System (NMIS) represents a strategic effort by hospitals to enhance the quality of nursing services through the digitalization of care documentation. However, during the early stages of implementation, the system may exert varying effects on nurses’ workload and the effectiveness of nursing services. This study aimed to analyze the influence of NMIS implementation on nurses’ workload and the effectiveness of nursing services, with user behavior as a mediating variable, in the inpatient wards of Khidmat Sehat Afiat Regional General Hospital, Depok City, in 2025. This study employed a quantitative analytical observational design with a cross-sectional approach. A total of 94 inpatient nurses were recruited using a total sampling technique. Data collection was carried out using a questionnaire, then analyzed using the Partial Least Square-based Structural Equation Modeling (SEM-PLS) method using SmartPLS 4.0. The results indicated that NMIS implementation had a positive and significant effect on user behavior and the effectiveness of nursing services, while demonstrating a negative and significant effect on nurses’ workload. User behavior was found to negatively and significantly influence nurses’ workload and positively and significantly affect the effectiveness of nursing services. Furthermore, nurses’ workload had a negative and significant impact on service effectiveness. Mediation analysis revealed that user behavior and nurses’ workload functioned as significant sequential mediators in the relationship between NMIS implementation and the effectiveness of nursing services. In conclusion, the optimal implementation of NMIS can contribute to reducing nurses’ workload and improving the effectiveness of nursing services.